Novel adipokine fibroblast growth factor 21 is increased in rheumatoid arthritis - Hulejová, Hana; Andrés Cerezo, Lucie; Kuklová, M; Pecha, Ondřej; Vondráček, Tomáš; Pavelka, Karel; Vencovský, Jiří; Haluzík, Martin; Šenolt, Ladislav (Physiological research, 2012)
Fibroblast growth factor-21 (FGF-21) has been recently characterized as a new adipokine. The aim of this study was to assess FGF-21 levels in patients with rheumatoid arthritis (RA) and osteoarthritis (OA) and to study the relationship between FGF-21, disease activity and metabolic status. The levels of FGF-21 in serum and synovial fluid samples from 38 patients with RA and 42 control individuals with OA were determined by ELISA. Patients were assessed for disease activity using the disease activity score (DAS28), a serum glucose and lipid profile. Age, sex and BMI-adjusted FGF-21 levels in the serum (p=0.024) and synovial fluid (p=0.010) samples were significantly higher in patients with RA when compared with OA. The levels of FGF-21 in the serum significantly correlated with the levels in the synovial fluid. Serum and synovial fluid FGF-21 levels adjusted for confounders correlated positively with C-reactive protein. The levels of FGF-21 were positively correlated with BMI in patients with RA; however, the levels were not associated with disease activity or lipid profiles. Furthermore, serum FGF-21 levels were significantly higher in seropositive compared with seronegative RA patients. This work shows that patients with seropositive RA have increased levels of FGF-21. The results suggest that FGF-21 is related to BMI but not disease activity or lipid profiles in patients with RA.
Keywords: fibroblastové růstové faktory; Arthritis, Rheumatoid; Female; biologické markery; revmatoidní artritida; Biomarkers; ženské pohlaví; Up-Regulation; Reproducibility of Results; Fibroblast Growth Factors; lidé; Sensitivity and Specificity; synoviální tekutina; upregulace; Adipokines; senzitivita a specificita; Humans; reprodukovatelnost výsledků; Male; Aged; index tělesné hmotnosti; Synovial Fluid; lidé středního věku; senioři; mužské pohlaví; Body Mass Index; Middle Aged; adipokiny